GATA6 Deficiency Leads to Epithelial Barrier Dysfunction and Enhances Susceptibility to Gut Inflammation. (10th August 2021) - Laudisi, Federica; Stolfi, Carmine; Bevivino, Gerolamo; Maresca, Claudia; Franzè, Eleonora; Troncone, Edoardo; Lolli, Elisabetta; Marafini, Irene; Pietrucci, Daniele; Teofani, Adelaide; Di Grazia, Antonio; Di Fusco, Davide; et al.
Abstract: Background and Aims: Intestinal barrier dysfunction is a hallmark of inflammatory bowel diseases [IBD], but the mechanisms that lead to such a defect are not fully understood. This study was aimed at characterising the factors involved in the defective barrier function in IBD. Methods: Transcriptome analysis was performed on colon samples taken from healthy controls [CTR] and IBD patients. Expression of GATA-binding factor 6 [GATA6], a transcription factor involved in intestinal epithelial cell differentiation, was evaluated in colon samples taken from CTR and IBD patients by real-time polymerase chain reaction [PCR] and immunohistochemistry. Intestinal sections of wild-type and Gata6del mice, which exhibit a conditional Gata6 deletion in intestinal epithelial cells and which are either left untreated or receive subcutaneous indomethacin or rectal trinitrobenzene sulphonic acid, were stained with haematoxylin and eosin. In parallel, some Gata6del mice received antibiotics to deplete intestinal flora. Mucosal inflammatory cell infiltration and cytokine production were evaluated by flow cytometry and real-time PCR, respectively, and tight junction proteins were examined by immunofluorescence. Intestinal barrier integrity was assessed by fluorescein isothiocyanate [FITC]-dextran assay. Results: Multiple genes involved in cell commitment/proliferation and wound healing were differentially expressed in IBD compared with CTR. Among these, GATA6 was significantly decreased in the IBD epithelium compared with CTR. In mice, conditional deletion of GATA6 in the intestinal epithelium induced primarily epithelial damage, diminished zonula occludens-1 expression, and enhanced intestinal permeability, ultimately resulting in bacteria-driven local immune response and enhanced susceptibility to gut inflammation. Conclusions: Reduced expression of GATA6 promotes intestinal barrier dysfunction, thus amplifying intestinal inflammatory pathology.